Brief Report: Renal replacement therapy in Korea, 2010 - Dong Chan Jin; Il Soo Ha; Nam Ho Kim; Seoung Woo Lee; Jong Soo Lee; Sung Ro Yoon; Byung Su Kim (The Korean Society of Nephrology, 2012)
The Korean Society of Nephrology (KSN) launched the official End-Stage Renal Disease (ESRD) Patient Registry in 1985 and the Internet online registry program was opened in 2001. The ESRD Registry Committee of KSN has collected data on dialysis therapy in Korea through the online registry program in the KSN Internet website. The increasing number of elderly people and diabetic patients in Korea has resulted in a very rapid increase in the number of ESRD patients. The total number of ESRD patients was 58,860 (hemodialysis [HD], 39,509; peritoneal dialysis [PD], 7309; and functioning kidney transplant [KT], 12,042). The prevalence of ESRD was 1144.4 patients per million population (PMP), and the proportion of renal replacement therapy was HD, 67.1%; PD, 12.4%; and KT, 20.5%. The number of new ESRD patients in 2010 was 9335 (HD, 7204; PD, 867; and KT, 1264; the incidence rate was 181.5 PMP). The primary causes of ESRD were diabetic nephropathy (45.2%), hypertensive nephrosclerosis (19.2%), and chronic glomerulonephritis (11.3%). The mean urea reduction ratio was 67.9% in male HD patients and 73.9% in female HD patients. The mean Kt/V was 1.394 in male patients and 1.659 in female patients. Five-year survival rates of male and female dialysis patients were 64.9% and 67.3%, respectively.